Neurogenesis and Alzheimer's Disease - Philippe Taupin (AboutScience Srl, 2006)
Alzheimer's disease (AD) is a neurodegenerative disease, characterized in the brain by amyloid plaque deposits and neurofibrillary tangles. It is the most common form of dementia among older people. There is at present no cure for AD, and current treatments consist mainly in drug therapy. Potential therapies for AD involve gene and cellular therapy. The recent confirmation that neurogenesis occurs in the adult brain and neural stem cells (NSCs) reside in the adult central nervous system (CNS) provide new opportunities for cellular therapy in the CNS, particularly for AD, and to better understand brain physiopathology. Hence, researchers have aimed at characterizing neurogenesis in patients with AD. Studies show that neurogenesis is increased in these patients, and in animal models of AD. The effect of drugs used to treat AD on neurogenesis is currently being investigated, to identify whether neurogenesis contributes to their therapeutic activities.